Price agreement and market provision between principal and distributor in the constitution no. 5, 1999 - Sukma, Ria Permata (Jurnal Hukum Volkgeist, 2019)
Market structure is one of the things that determines potential occurance of price fixing. Market characteristics with large entry barriers for newcomers causing difficulties for competitors to enter so that there are no substitutes. Distributor is one of the business actors namely a national trading company that acts for and in its own name based on an agreement with the principal to make purchases, storage, sales and marketing of goods and/or services. There are pricing activities in business activities carried out by distributors with their networks in controlled markets, so the main issue in this study is whether the pricing is included in the price fixing agreement which is prohibited by the Law Prohibition of Monopolistic Practices and Unfair Business Competition. The approach used to analyze the problem is statute and conceptual approach to examine and find legal concepts that are relevant to the issues raised, thus finding a way out and produce solution for business actors to become more competitive and avoid anti-competitive behavior.business competition, price fixing, market share, distributors, principals